Anemia and Social Determinants of Health: An Opportunity for Primary Healthcare: Anemia y determinantes sociales de la salud: Una oportunidad para el primer nivel de atención - Morales, Juan (2019)
In primary healthcare facilities (PHFs) in large cities such as Lima and Callao, outreach work is carried out in close proximity to the facilities, without the need to walk or travel for hours—sometimes on pack animals—to reach destinations, as occurs in many facilities in the interior of the country. Within the PHFs, there are undoubtedly healthcare workers willing to confront this challenge—committed professionals in whose hands, together with the community, lies the success of combating anemia. Therefore, anemia represents an opportunity for all those involved in primary healthcare to engage and promote a paradigm shift that enables a positive influence on other social determinants of health, thereby reducing anemia and other health problems.